The formation and development of social responsibility of business: Ukrainian experience in a context of decentralization - Pochtovyuk Andrew; Semenikhina Victoria; Onyshchenko Oksana; Ruban Bogdan (SHS Web of Conferences, 2019)
The current trends of using the practice of social responsibility (SR) and sustainable business in the world and in Ukraine in particular have been considered by the authors. The researches of business social responsibility policy in the field of sustainable development considered as a single international standard have been made. As well as the prospects of social responsibility in business development in the context of power decentralization in Ukraine have been considered.